The Educational Value Of Wayang Kulit Gagrak Porongan - Shiddhiqy, Ahmad Maulana Iqbal (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This study aims to analyze the educational values contained in the Porongan puppet show, as well as explore the contribution of puppeteer Ki Suwoto Ghozali in developing the art of puppet puppetry in Porongan. The research method used is the ethnographic historical method. The primary source is taken from the biographical records of the puppeteer Ki Suwoto Ghozali in the form of audio and video recordings of puppet performances and strengthened through interviews with students and followers of Ki Suwoto Ghozali. Secondary sources are in the form of analysis of various journal articles and literature books relevant to the topic. The results of the study show that Porongan puppets in addition to functioning as an entertainment art, also contain positive and significant educational values. These values are reflected in the floats, janturan, and prabatilarsa sendhon sessions created by puppeteers. Porongan puppet is able to reflect adaptation to the social and political situation during the old and new order periods. Unique characteristics such as the use of the East Javanese language and the distinctive coloring of Porongan puppets add to the cultural richness contained in the performing arts. This research emphasizes the importance of preserving Porongan puppet puppets as a cultural heritage rich in educational and philosophical values that reflect the identity and local wisdom of the Sidoarjo community, as well as offering a valuable contribution to the art of puppet performances as part of the noble culture of the Indonesian nation.